Corrosion fatigue of Ti‐6Al‐4V coupons manufactured by directed energy deposition. Issue 7 (18th April 2022) - Hattingh, Danie G.; Botha, Sheldyn; Bernard, Dreyer; James, M. Neil; du Plessis, Anton
Abstract: Titanium is a versatile biocompatible metal that is desirable in additively manufactured medical implant devices. However, additively manufactured parts have particular microstructures, porosity, residual stress, and surface conditions which can have a strong impact on fatigue performance. Implants have an added complexity from the saline operating environment and the associated impact on the safe design life. Equally, direct energy deposition induces a complex thermal history which, if not carefully controlled, can significantly alter the mechanical/material properties of the component. This study investigates the decrease in fatigue life, in an in vitro body fluid simulation using Ringer's solution, observed in Ti‐6Al‐4V specimens extracted from coupons manufactured by directed energy deposition. An interrupted deposition strategy was employed to control build regularity, which appeared to influence certain mechanical properties, including corrosion fatigue life. An ≈50% decrease in fatigue life was observed in Ringer's solution at 6 Hz loading frequency, clearly important in designing implants. Highlights: Interrupted build strategy was employed to control build regularity. In situ heat treatment resulting from build strategy contributes to a more homogenous microstructure. A reduction in fatigue life from the in vitro simulation medium was observed. X‐ray CT data show link between fatigue life and thermal history.